2015
DOI: 10.1371/journal.pone.0135337
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Characterization of Microalgae and Microalgae Mixtures Using Matrix-Assisted Laser Desorption Ionization Time-Of-Flight Mass Spectrometry (MALDI-TOF MS)

Abstract: Current molecular methods to characterize microalgae are time-intensive and expensive. Matrix Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) may represent a rapid and economical alternative approach. The objectives of this study were to determine whether MALDI-TOF MS can be used to: 1) differentiate microalgae at the species and strain levels and 2) characterize simple microalgal mixtures. A common protein extraction sample preparation method was used to facilitate rapid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Model mixtures of microalgae produced spectra with peaks not found in the spectra of individual microalgae composing the mixture—Fig. . The biochemical origin of these mixture‐specific peaks is unclear, and their possible utility in mixture characterization warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model mixtures of microalgae produced spectra with peaks not found in the spectra of individual microalgae composing the mixture—Fig. . The biochemical origin of these mixture‐specific peaks is unclear, and their possible utility in mixture characterization warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI mass spectra of monoalgal cultures of (A) Chlorella vulgaris UTEX 395, (B) Scenedesmus acutus LRB‐AP 401, and (C) Chlorella sorokiniana UTEX 1230 lack biomarkers, for example, at m/z 11 048 and m/z 11 230, observed in (D) a binary mixture of Chlorella vulgaris UTEX 395 and Scenedesmus acutus LRB‐AP 401 and (E) a tertiary mixture of all three microalgae. Reprinted with permission from Barbano et al…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of microorganisms from mixed or complex samples derived, for example, from patients, the environment, or infected plant tissue or food by MALDI-TOF MS is an important goal. So far, only a few reports have demonstrated the identification of bacteria and microalgae in mixtures by using biomarkers or correlation coefficients [83][84][85]. These studies have shown that ion suppression can affect the detection of specific masses of one or the other microorganism and thus complicate species identification in mixed samples [83,84,86].…”
Section: Maldi-tof Ms Of Polymicrobial Samples and Infected Materialsmentioning
confidence: 99%
“…So far, only a few reports have demonstrated the identification of bacteria and microalgae in mixtures by using biomarkers or correlation coefficients [83][84][85]. These studies have shown that ion suppression can affect the detection of specific masses of one or the other microorganism and thus complicate species identification in mixed samples [83,84,86]. On the other hand, novel mass peaks only observed in the mixed sample were discovered and may serve as biomarkers for mixtures or contaminations [83,86].…”
Section: Maldi-tof Ms Of Polymicrobial Samples and Infected Materialsmentioning
confidence: 99%
See 1 more Smart Citation